PREFORMULASI: KONSENTRASI AMILUM BUAH PISANG SINGALI-NGALI (Musa Acuminata Lady Finger) SEBAGAI BAHAN PENGIKAT TERHADAP TABLET PARACETAMOL METODE GRANULASI BASAH YANG MEMENUHI PERSYARATAN FARMAKOPE - Sinaga, Alex; Auliafendri , Novycha; Sabina, Fitri (JIFI (Jurnal Ilmiah Farmasi Imelda), 2025)
Currently, bananas can be processed and used to produce starch. Research results show that bananas have a lot of nutrients per 100 grams. There is 99 kcal of energy, 1.2 grams of protein, 0.2 grams of fat, 93% carbohydrates, 2.93% water (Shekhara Naik R et al., 2023). Because of their carbohydrate content, bananas can be made into starch. These bananas will be used as the main ingredient to make banana starch. This starch can be used in the pharmaceutical industry as an additional ingredient for making tablets because of its properties as a binder, disintegrant and filler. The aim of this research was to determine the effect of the concentration of Singali-Ngali banana starch (Musa Acuminata Colla) as a binding agent in granule evaluation tests that meet the requirements of the VI edition of the Pharmacopoeia. This research method is included in quantitative experimental research, which is carried out in the laboratory. The stages of this research started from sample preparation, making banana starch, characteristics test, carbohydrate test, pre-formulation, granule evaluation test and paracetamol tablet evaluation test from singali ngali banana binder. The results obtained from the Singali Ngali banana binder can have a positive influence with the p value 0,05 at a CL value of 95% From the conclusion, all formulas meet the requirements as binders